2017
DOI: 10.1186/s13561-017-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification determinant factors on willingness to pay for health services in Iran

Abstract: BackgroundA common method used to examine the relationship between internal preferences and caring externalities is willingness to pay (WTP) approach. We aimed to estimate WTP for health status with different severity level and identify determinant factors on WTP.MethodsFor determining main factors in WTP, a cross-sectional study was conducted in Shiraz in the southeast of Iran, in March to April 2015. The open-ended method was used to estimate monthly WTP in private and altruistic section. Multivariate regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
3
17
1
Order By: Relevance
“…This may be due to those having more income may had additional money to be allocated for promotion of their health in addition to basic needs. Studies conducted in Addis Ababa [23], Malaysia [20] Iran [15], Korea [26] and USA [27] for different health care services supported this evidence.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This may be due to those having more income may had additional money to be allocated for promotion of their health in addition to basic needs. Studies conducted in Addis Ababa [23], Malaysia [20] Iran [15], Korea [26] and USA [27] for different health care services supported this evidence.…”
Section: Discussionmentioning
confidence: 79%
“…This may be due to study population difference which may not have equal information about health. However, the result of the study was lower than willingness of respondents to pay for health service in Iran which was 88.8% [15]. The possible reason might be difference in study areas, cultural and demographic and study population differences.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of various studies performed in both developing and developed countries have also confirmed the effect of the households' economic status on their being faced with poverty and CHE (16,22,23). Another study shows that households with higher income had a higher willing to pay and access ability to health services (24). Poverty reduction policies, which improve the level of total household welfare, can be helpful as well.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, for self-paid vaccination such as pneumonia and influenza vaccines, the individuals with the highest ability to pay had 18 times higher WTP value than those with the lowest ability to pay [32]. Others reported the monthly income as a key factor affecting the WTP [19]. However, the WTP values considerably vary with income, and the low-and middle-income countries had lower WTP compared to the high-income countries [25].…”
Section: Discussionmentioning
confidence: 99%
“…The first part employed a self-administrated questionnaire to obtain data on sociodemographic characteristics, including the children's gender, mothers' age, and educational level, households' monthly income, and health insurance coverage. The second part of the study elicited the mothers' openended WTA and WTP values for vaccines to their children as recommended in other studies [19,20]. With the understanding that the EPI service is free of charge, we involved the mothers in the study after getting their children immunized.…”
Section: Data Collection and Variablesmentioning
confidence: 99%